(untitled) (Iranian Journal of Kidney Diseases, 2010)
Introduction. This study evaluated the health-related quality of life (HRQOL) in a sample of Iranian patients undergoing maintenance hemodialysis. The data were compared with the HRQOL for the Iranian general population. Materials and Methods. Two-hundred and fifty patients undergoing hemodialysis were included using a convenience sampling approach in a cross-sectional study. Data collection was performed using a Persian translation of the Short Form-36 questionnaire in combination with demographic and clinically related questions. The collected data were analyzed using a logistic regression model with physical and mental summary scales as dependent variables. Results. The patients’ mean Short Form-36 scores were significantly lower than those obtained for the general population for all scales. Patients with longer duration of being on hemodialysis, poor adherence to treatment, higher body mass index, and comorbidity diseases suffered from a poorer physical health. Poor mental health was associated with a lower level of education, longer duration of hemodialysis, lower economic status, a lower degree of knowledge on disease, and comorbidity diseases. Conclusions. This study affirms the fact that patients undergoing hemodialysis suffer from poor HRQOL. In comparison with data from other studies from Asian and European countries, this sample of Iranian patients on hemodialysis had a lower HRQOL, a discrepancy that might be due to differences in life style, socioeconomic status, the general level of education of the patients, as well as physician-patient communication.